2007
DOI: 10.1007/s10666-006-9078-y
|View full text |Cite
|
Sign up to set email alerts
|

Directional Connectivity of Wolf (Canis lupus) Populations in Northwest Spain and Anthropogenic Effects on Dispersal Patterns

Abstract: In view of the extensive information available on wolf ecology and habitat suitability, and on the fragmentation of wolf populations by motorways and similar infrastructures, a key factor in their conservation, the aim of the present study was to model the directional connectivity of wolf populations in the region of Galicia in northwest Spain, and to quantify anthropogenic effects on wolf dispersal patterns. To this end, we map the probability of wolf movement by means of known relationships between wolf move… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…By either allowing or preventing the dispersal of individuals from the introduction site, we considered an extreme case where landscape features would correspond to insurmountable barriers in natura. These barriers can be anthropogenic (Rodriguez‐Freire and Crecente‐Maseda ), but they can also be natural landscape features (Rueness et al ) or variations in environmental conditions (Winemiller et al ). In the context of introduced populations, such as the use of biological control agents in agriculture, landscape elements like windbreaks, hedgerows or ditches, can act as barriers to dispersal (Lovei et al , Wratten et al ).…”
Section: Discussionmentioning
confidence: 99%
“…By either allowing or preventing the dispersal of individuals from the introduction site, we considered an extreme case where landscape features would correspond to insurmountable barriers in natura. These barriers can be anthropogenic (Rodriguez‐Freire and Crecente‐Maseda ), but they can also be natural landscape features (Rueness et al ) or variations in environmental conditions (Winemiller et al ). In the context of introduced populations, such as the use of biological control agents in agriculture, landscape elements like windbreaks, hedgerows or ditches, can act as barriers to dispersal (Lovei et al , Wratten et al ).…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, knowledge about minimal requirements for the survival of wolves, comprising land cover, food availability and human influences, are essential. Wolf habitat models can help to gain this information and improve the carnivore's conservation by determining priority areas, developing conservation corridors between important wolf habitats and highlighting potential conflict zones between wolves and humans (Kramer-Schadt et al, 2005;Rhodes et al, 2006;Rodriguez-Freire and Crecente-Maseda, 2008). The aim of our study was, therefore, to develop a habitat model based on data about wolf presence in central northern Portugal and gain insight into potentially important environmental factors (biotic and abiotic) for wolf distribution, with a particular emphasis on the impact of anthropogenic variables on the predator's presence.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the uncertainty about the maximum dispersal distance of the wolf, we tested two Euclidean distance thresholds: 100 km (low dispersal ability) and 850 km (high dispersal ability) [31]. We chose these two threshold distances because the mean wolf dispersal distance has been reported to range from about 13 to about 80 km [54,55], but occasionally individuals may travel much longer distances reaching 840-866 km [55,56]. In addition, genetic analyses performed on European wolf populations have revealed that the range of spatial influence is 650-850 km, meaning that the genetic diversity of a wolf population is influenced by populations up to 850 km apart [12].…”
Section: Modeling Connectivitymentioning
confidence: 99%